Effects of vomitoxin concentration in nursery pig diets and the effectiveness of commercial products to mitigate its effects - J A Barnes; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 180 pigs (PIC TR4 x 1050, initially 22.8 lb and 34 d of age) were used in a 21-d trial to evaluate the effects of vomitoxin concentration in nursery pig diets and the effectiveness of commercial products to mitigate vomitoxin's negative effects on performance. Pens of pigs were balanced by initial weight and were randomly allotted to 1 of 5 dietary treatments with 6 replications per treatment. Dietary treatments included a control diet consisting of corn-soybean meal and regular dried distillers grains with solubles (DDGS; low vomitoxin), a negative control diet containing 4 ppm dietary vomitoxin (from contaminated DDGS), and the negative control diet with Biofix Plus, Cel-can with bentonite clay, or Defusion Plus. All diets were fed in meal form. From d 0 to 10, pigs fed either the negative control or diets containing Biofix Plus, Celcan with bentonite clay, or Defusion Plus had decreased (P<0.05) ADG and ADFI than pigs fed the positive control diet. Pigs fed the positive control diet had improved F/G (P<0.05) compared to pigs fed the negative control diet and diets containing Biofix Plus or Cel-can with bentonite clay, with pigs fed diets containing Defusion Plus intermediate. From d 10 to 21, pigs fed the positive control or diet containing Defusion Plus had greater (P<0.05) ADG than the negative control, Biofix Plus, and Cel-can with bentonite clay diets. Additionally, pigs fed the positive control diet had a greater (P<0.05) ADFI than pigs fed the negative control and diets containing Biofix Plus and Cel-can with bentonite clay, with pigs fed Defusion Plus intermediate. Overall (d 0-21), pigs fed the positive control diet had greater (P<0.05) ADG compared to pigs fed any of the vomitoxin-contaminated diets. In addition, pigs fed diets containing Defusion Plus had greater ADG (P<0.05) than pigs fed the negative control diet and diets containing Biofix Plus or Cel-can with bentonite clay. Pigs fed the positive control diet had greater ADFI (P<0.05) than pigs fed any other dietary treatment. Pigs fed the positive control diet had improved F/G (P<0.05) compared to the negative control and diets containing Biofix Plus or Cel-can with bentonite clay. Also, pigs fed Defusion Plus had improved F/G (P<0.05) compared to pigs fed the negative control. Thus, nursery pigs fed diets containing 4 ppm vomitoxin had reduced growth performance. Including Defusion Plus in the diet improved performance but not to that of pigs fed a low-vomitoxin diet.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Biofix Plus; Cel-can with bentonite clay; Defusion Plus; Vomitoxin